DIAGNOSTIC VALUE OF THE REACTION AT THE BACILLUS CALMETTE-GUÉRIN VACCINATION SITE IN KAWASAKI DISEASE - Lilian Martins Oliveira Diniz; Raquel Gomes Castanheira; Yala Gramigna Giampietro; Matheus Sewastjanow Silva; Flávia Duarte Nogueira; Priscila Duarte Pessoa; Thamires Marx da Silva Santos; Gislene Soares Coutinho; Roberta Maia de Castro Romanelli (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To describe the case of an infant - diagnosed with incomplete Kawasaki disease - who developed BCG scar reactivation. Case description: A 6-month-old patient was admitted to hospital with fever associated with ocular hyperemia, cervical lymphadenopathy, and hyperemic lips, and remained hospitalized for 12 days. The physical examination revealed an inflammatory reaction at the site of the BCG scar, leading to the diagnosis of incomplete Kawasaki disease. The patient was treated with venous immunoglobulin, but presented recurrence of Kawasaki disease, with subsequent onset of coronary artery disease. Comments: BCG scar reactivation is an important finding in countries where the vaccine is routinely given and may be a useful marker for early diagnosis of Kawasaki disease, especially in its incomplete form.